Cold agglutinin isotypes - Kreft, Heidi; Hack, Hildegard; Roelcke, Dieter (Transfusion medicine and hemotherapy, 1999)
Background: Although it is known that IgM κmoleculespredominate in cold agglutinins (CAs), exact data on thefrequency of Ig classes and L-chain types (isotypes) ofCAs and their distribution among CAs with differentspecificities are missing. Material and Methods: 384 CAsof our collection were tested for isotypes by double dif-fusion or 2-mercaptoethanol treatment. CA specificitieswere determined using untreated, papain- and sialidase-treated red blood cells derived from human adults andnewborns. Anti-Pr subspecificities were defined bychemically modified glycophorins and further character-ized by specifically α2,3-desialylated red cells. Results:Almost all anti-I CAs are IgM. Almost all IgG and IgA ex-amples are anti-Pr CAs, most of which are IgM. IgG andIgA CAs apparently accumulate within CAs with anti-Pr1hand anti-Prasubspecificities. λ-type IgM CAs are foundamong anti-I (6.5%) and anti-Pr CAs (8.7%) but are pref-erentially associated with anti-i CAs (20.6%). Conclusion:Ig class switching is rare in CAs. It is decisive for themode and extent of red blood cell destruction. Autoim-mune hemolysis due to IgM CAs is complement mediat-ed. Red blood cell destruction induced by IgG CAs differsfrom that caused by IgM CAs, whereas IgA CAs do notcause (intense) immune hemolysis. CA class switching isassociated with CA (sub)specificities. They reflect au-toantigens capable of inducing class switching.